Gate-defined quantum confinement in InSe-based van der Waals heterostructures - Hamer, Matthew James; Tovari, Endre; Zhu, Mengjian; Thompson, Michael; Mayorov, Alexander; Prance, Jonathon; Lee, Yongjin; Haley, Richard P.; Kudrynskyi, Zakhar R.; Patanè, Amalia; Terry, Daniel; Kovalyuk, Zakhar D.; et al. (American Chemical Society, 2018)
Indium selenide, a post-transition metal chalcogenide, is a novel two-dimensional (2D) semiconductor with interesting electronic properties. Its tunable band gap and high electron mobility have already attracted considerable research interest. Here we demonstrate strong quantum confinement and manipulation of single electrons in devices made from few-layer crystals of InSe using electrostatic gating. We report on gate-controlled quantum dots in the Coulomb blockade regime as well as one-dimensional quantization in point contacts, revealing multiple plateaus. The work represents an important milestone in the development of quality devices based on 2D materials and makes InSe a prime candidate for relevant electronic and optoelectronic applications.